From temple to house of movement and dance; adaptive reuse of redundant church in Copenhagen to modern city needs - Binerowska, Marta (My University, 2025)
In the face of increasing secularization and a declining number of believers, many European churches are losing their original function and becoming redundant. These buildings are often buildings of great architectural and cultural value, and their reuse is of great importance in terms of both heritage preservation and social sustainability. The subject of this thesis is the adaptive reuse of one of the redundant churches in Copenhagen into new functional spaces that meet the needs of modern cities. The thesis uses both research for design and research by design in order to achieve the best possible results. The work analyzes the needs of the local community and explores possible functional programs, ultimately proposing a new function that meets the requirements of contemporary users, which is the “House of Movement and Dance.” The design proposal integrates contemporary architectural interventions with the original structure of the building, respecting the cultural heritage, and creating sensory environments that enhance the spatial experience and support movement activities in the adapted space.
Keywords: Adaptive Reuse, Church Transformation, Sensory Architecture, Heritage